SOLAR, INDUSTRIAL PROCESS-HEAT APPLICATIONS IN SELECTED TURKISH INDUSTRIES - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1992)
We discuss the potential and economic feasibility of solar, industrial process-heat applications in the Turkish food, textile and chemical industries. The study covers 18 sites and end-use temperatures up to 120 and 150-degrees-C. A solar system composed of parabolic troughs but without thermal storage and to be backed up by the existing conventional boiler is chosen. The system-size range investigated is 500-20,000 m2. The economic criteria applied are net present value analysis and the determination of internal rate of return. Break-even net fuel prices and break-even system sizes, which make the net present value equal to zero, are also calculated. Levelized energy-costs analysis and the method of the discounted pay-back period have been included in the study.
Keywords: ENERGY-REQUIREMENTS